Sistem Pendukung Keputusan Penentuan Model Pembelajaran Untuk Guru Dengan Metode Analytical Hierarchy Process (Studi Kasus: SMK Pgri Telagasari) - Annisa Nurjanah; Arip Solehudin; Aji Primajaya (Peneliti.net, 2022)
The selection of the right learning model will make it easier for teachers to improve the quality of learning and make it easier for students to understand the learning material. However, choosing the right learning model is not an easy thing to do. In determining the learning model, the teacher must first learn about the learning model and make several considerations that take a lot of time. Therefore, this study aims to build a decision support system that can help teachers to get recommendations for learning models that are appropriate to the situation and condition of their students. The decision support system method used in this study is the Analytical Hierarchy Process method. The learning model used in this research is problem based learning, project based learning, and discovery learning. The system is built on a web-based basis with the PHP programming language and MySQL database. The results of this study conclude that the AHP method can assist teachers in solving decision-making problems in the learning model determination system.